Core-Level Photoelectron Spectroscopy of Metal Clusters at FLASH. (August 2015) - Martinez, F; Oelßner, P; Köther, M; Tiggesbäumker, J; Meiwes-Broer, K H; Bauer, D; Ganteför, G; v. Issendorff, B; Meyer, M; Müller, T; Rühl, E
Synopsis: Free size-selected metal clusters are investigated by core-level photoelectron spectroscopy at the free electron laser FLASH. The binding character of the clusters, as well as a multitude of relaxation channels are indicated by size- dependent core-level shifts and low-energy secondary electron emission, respectively. A new apparatus including a cryogenic ion-trap is currently built to extend the studies towards the smallest cluster sizes (less than 10 atoms), where low photo-absorption cross sections have to be matched by increased cluster density.